Hubungan Thoracic Fluid Content Cardiometry dengan Lung Ultrasound Score untuk Menilai Lung Water pada Pasien Pascaoperasi Mayor di ICU - Pradana, Gilar Rizki Aji; Jufan, Akhmad Yun; Wisudarti, Calcarina Fitriani Retno (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2021)
Background: Perioperative fluid management in patients undergoing major surgery is important. Excessive administration of fluid can cause atrial natriuretic peptide release and iatrogenic glycocalyx/vascular endothelial junction dysfunction which can cause intravascular fluid shifting to the extravascular space. This fluid shifting can occur in the pulmonary interstitial space. Lung Ultrasound Score (LUS) score and Thoracic Fluid Content (TFC) examination with ICON is considered suitable to assess Extravascular Lung Water (EVLW). Objective: To determine the correlation between the LUS score with TFC using ICON in post-operative major patients in the ICU. Methods: A prospective observational research design with a cross-sectional study design. The sample size was 30 adult post-major surgery patients who were treated in the ICU of Dr. Sardjito. The LUS score was obtained from an ultrasound examination of the lungs and TFC was assessed with the ICON device. LUS examination was performed at 3-4 and 7-8 intercostal space between the parasternal-mid clavicular line, and on the lateral side at the level of the mid-axillary line. Correlation analysis was conducted to determine the degree of correlation between LUS score and TFC. Results: The sample of this study was 30 patients. Mean age 46.40±12.30 years, P/F ratio 411,21±77,64, AaDO2 121,20±53,4, LUS score 3.30±2.58, and TFC 24.56±10.30. Fluid balance during operation 194,2±756,65. The Spearman correlation test between LUS score and TFC showed a positive and significant correlation between LUS score and TFC, p<0.001 and r=0.703. The Spearman correlation test for LUS score and P/F ratios, LUS score and AaDO2, LUS score and fluid balance in the operating room showed no significant relationship (p>0.05). Conclusions: The correlation between LUS score and TFC values in postmajor surgery patients treated in the ICU was statistically significant (p<0.001) and the correlation was positive (r=0.703).